ANALYSIS OF FARMERS' INCOME AFFECTED ATTACKS OF PLANT DISTURB ORGANISMS IN SUSOH DISTRICT SOUTHWEST ACEH DISTRICT - Sufriadi; Yossi Mardhiah; Aswin Nasution; Hasan Husein (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Paddy field in Susoh District, Southwest Aceh Regency are very vulnerable to the impacts of climate change such as drought and floods which have caused the intensity of attacks by Paddy field Pest Organisms (OPT) decreased as it had in the previous growing season. Some farmers make mitigation efforts by spraying pesticides according to the recommendations of the local Plant Pest Organism Observer (POPT), but some other farmers do not carry out mitigation due to considerations of production costs that are quite large and ultimately affect the total revenue and income of farmers. This study aims to look at the differences in total production and average income between farmers who mitigate and farmers who do not mitigate pest attacks. The sample was divided into two categories, each category was taken by 28 farmer respondents randomly. The results of the independent test sample t-test on production obtained t-count (4.056) greater than t-table () while for income obtained t-count (4.056) greater than t-table (2.46) indicating there is a difference in production and average income between mitigating and non-mitigating farmers. Total GKP production obtained by mitigating farmers was an average of 2.608 tons and farmers who did not mitigate an average of 2.011 tons. The average income of farmers who mitigate pest attacks is IDR 4,821,834.79 per 0.4 hectare or IDR 12,054,600 per hectare, while farmers who do not mitigate pest attacks are IDR 2,888,103.86 per 0.4 hectare or IDR 7,220,260 per hectare per planting season.